1264 AN ANALYSIS OF CONSULTANT JOB ADVERTS IN GERIATRIC MEDICINE IN ENGLAND AND WALES. (16th January 2023) - Monnier-Hovell, Z; Jundi, A; Sims, H; Sheikh, A
Abstract: Introduction: The British Geriatrics Society (BGS) Flexible Workforce Statement supports national policy such as the NHS People Plan in promoting less than full time (LTFT) working. 1, 2 As LTFT trainee representatives on the BGS Trainees' Council we were interested to know how consultant work patterns are advertised. We analysed job adverts for Consultants in Geriatric Medicine over a two-year period to identify how many were LTFT posts. Method: A freedom of information (FOI) request was submitted to online recruitment website 'NHS Jobs'. The request identified jobs in 'Elderly Care Medicine' OR those containing 'Geriatric' in their title between 01/04/2019 and 31/03/2021. The FOI data were filtered to only include Consultant posts, grouped by training deanery and analysed using Excel. Regional numbers of LTFT trainees were identified by emailing Training Programme Directors and a FOI request to deaneries for non-responders. The number of LTFT consultants was identified using the online Royal College of Physicians census. 3 Results: The FOI request returned 7589 jobs; of these 1083 were consultant posts. These ranged from 42 in Thames Valley to 171 in East of England. Twenty-one jobs (1.9%) were advertised as LTFT, the highest proportion was 10.5% in Yorkshire and Humber. Twenty-eight (2.6%) were negotiable, the highest proportion was 15.9% in the South West. On average, 33% of LTFT jobs were advertised as permanent posts. Currently, 37.7% of trainees, and 25% of consultants, work LTFT. Conclusion: Number of LTFT job adverts was low compared to the number of LTFT consultants and trainees, although there is regional variation. A limitation was that details of adverts were not seen, which made it unclear whether each job was a fresh advert or readvertising an unfilled post. The latter is likely given there are 1747 consultants working in the UK. 3 Further avenues of work include identifying LTFT opportunities for SAS grade doctors and allied health professionals. References: 1. https://www.england.nhs.uk/ournhspeople/online-version/lfaop/ 2. https://www.bgs.org.uk/resources/flexible-working-in-geriatric-medicine 3. https://www.rcplondon.ac.uk/projects/outputs/working-differently-shadow-covid-19-uk-2021-census-consultant-higher-specialty